Monitoring of renewable energy yield of mixed wastes by image analysis of input residual waste materials - Wagland, Stuart T.; Longhurst, Philip J. (CISA Publisher, 2012)
A novel image analysis method has been developed by Cranfield University. Following on from a recent study, this approach has been applied alongside calorific values and %14C to determine the renewable energy content of mixed wastes. This method determines the composition of the mixed waste material, and then using calorific values and biogenic carbon (14C) content the renewable energy potential of the mixed waste sample can be accurately determined. The correlations between actual (known) weights and composition of the components and the values from the image analysis are compared; these correlations (r ≥0.988) were found to be highly significant (p<0.005). The renewable energy contents (as a % of the total energy) were calculated to be between 0.64 and 3.98 below the actual values. Potential applications for the image analysis tool include a) renewable energy potential of mixed wastes prior to combustion, and b) certification of solid recovered fuels [SRF].